Foreign Direct Investment and the Domestic Capital Stock - Desai, Mihir A; Foley, C. Fritz; Hines, James R (American Economic Review, 2005)
Rising levels of foreign direct investment (FDI) concern growing numbers of policymakers and members of the American public. These concerns stem from the perception that foreign activities of American multinational corporations reduce employment and other economic activities within the United States. While investment flows within the United States go largely unnoticed, in an international setting the lexicon of “winners” and “losers” can be inescapable. Curiously, both capital-exporting countries and capital-importing countries have at times expressed concern over the consequences of international capital flows. Capital-exporting countries worry that too much of their capital goes abroad, while capital-importing countries fear foreign control of domestic assets and the possible macroeconomic instability associated with rapid changes in foreign investment levels. The concerns of capital-exporting countries, while diffuse, often are based on conceptions of outbound FDI as diverting economic activity. Unsurprisingly, growing overseas activities of multinational firms have become a source of economic insecurity for workers, managers, and tax collectors (see e.g., Kenneth F. Scheve and Matthew J. Slaughter, 2001).